Efforts towards overcoming drought stress in crops: Revisiting the mechanisms employed by plant growth-promoting bacteria - Fadiji, Ayomide Emmanuel; Santoyo, Gustavo; Yadav, Ajar Nath; Babalola, Olubukola Oluranti (Frontiers in Microbiology, 2022)
Globally, agriculture is under a lot of pressure due to rising population and corresponding increases in food demand. However, several variables, including improper mechanization, limited arable land, and the presence of several biotic and abiotic pressures, continually impact agricultural productivity. Drought is a notable destructive abiotic stress and may be the most serious challenge confronting sustainable agriculture, resulting in a significant crop output deficiency. Numerous morphological and physiological changes occur in plants as a result of drought stress. Hence, there is a need to create mitigation techniques since these changes might permanently harm the plant. Current methods used to reduce the effects of drought stress include the use of film farming, super-absorbent hydrogels, nanoparticles, biochar, and drought-resistant plant cultivars. However, most of these activities are money and labor-intensive, which offer limited plant improvement. The use of plant-growth-promoting bacteria (PGPB) has proven to be a preferred method that offers several indirect and direct advantages in drought mitigation. PGPB are critical biological elements which have favorable impacts on plants' biochemical and physiological features, leading to improved sugar production, relative water content, leaf number, ascorbic acid levels, and photosynthetic pigment quantities. This present review revisited the impacts of PGPB in ameliorating the detrimental effects of drought stress on plants, explored the mechanism of action employed, as well as the major challenges encountered in their application for plant growth and development.